Prognostic value of humoral markers in patients with anthracycline-related cardiac dysfunction - E. V. Grakova; K. V. Kopeva; S. N. Shilov; E. T. Bobyleva; E. N. Berezikova; V. V. Kalyuzhin; A. T. Teplyakov (Бюллетень сибирской медицины)
Aim. To carry out a 12-month study on the prognostic role of humoral markers responsible for the main mechanisms of initiation of cardiotoxic myocardial damage (endothelin-1, soluble Fas-L, N-terminal pro-brain natriuretic peptide (NT-proBNP), tumor necrosis factor-α, interleukin (IL)-1β, matrix metalloproteinase (MMP)-2 and MMP9, soluble form of the ST2 protein (sST2), a tissue inhibitor of metalloproteinase-1, and tetranectin) in assessing the risk of progression of anthracycline-related left ventricular dysfunction.Materials and methods. The study included a total of 114 women aged 48.0 (46.0; 52.0) years without concomitant cardiovascular diseases and risk factors who received chemotherapy with anthracyclines in the past. The levels of serum biomarkers were determined using the enzyme immunoassay. Transthoracic echocardiography was performed at baseline and at 12 months of follow-up.Results. After 12 months of follow-up, all patients were retrospectively divided into 2 groups: group 1 (n = 54) included patients with an unfavorable course of anthracycline-related cardiac dysfunction (ARCD), group 2 (n = 60) encompassed patients with a favorable course of the disease. According to the ROC analysis, MMP-2 ≥ ≥ 338.8 pg / ml (sensitivity 57%, specificity 78%; AUC = 0.629; p = 0.025), MMP-9 ≥ 22.18 pg / ml (sensitivity 89%, specificity 87%; AUC = 0.886; p < 0.001), sST2 ≥ 32.4 ng / ml (sensitivity 64%, specificity 70.5%; AUC = 0.691; p = 0.002), and tetranectin ≤ 15.4 pg / ml (sensitivity 69%, specificity 72%; AUC = 0.764; p < 0.001) were identified as predictors of an adverse course of ARCD. When comparing ROC curves, it was found that the concentration of MMP-9 (p = 0.002) was the most significant predictor of the progression of ARCD.Conclusion. MMP-2 and -9, soluble ST2, and tetranectin can be considered as non-invasive markers for assessing the risk of ARCD progression. At the same time, an increased level of MMP-9 is the most significant predictor of ARCD progression.